Simulating record-shattering cold winters of the beginning of the 21st century in France - C. Cadiou; P. Yiou (Weather and Climate Dynamics)
Extreme cold winter temperatures in Europe have huge societal impacts. Being able to simulate worst-case scenarios for such events for present and future climates is hence crucial for short- and long-term adaptation. In this paper, we are interested in persistent cold events, whose probability will decrease with climate change. Large ensembles of simulations allow us to better analyse the mechanisms and characteristics of such events but can require significant computational resources. Rather than simulating very large ensembles of normal climate trajectories, rare-event algorithms allow the sampling of the tail of distributions more efficiently. Such algorithms have been applied to simulate extreme heat waves. They have emphasized the role of atmospheric circulation in such extremes. The goal of this study is to evaluate the dynamics of extreme cold spells simulated by a rare-event algorithm. We focus on cold winter temperatures that have occurred in France from 1950 to 2021. We investigate winter mean temperatures (December, January and February) and identify a record-shattering event in 1963. We find that although the frequency of extreme cold spells decreases with time, their intensity is stationary. We apply a stochastic weather generator (SWG) approach with importance sampling to simulate the coldest winters that could occur in a factual and counterfactual climate. We thus simulate ensembles of the worst winter cold spells that are consistent with reanalysis data. We find that a few simulations reach colder temperatures than the historical record-shattering event of 1963. This shows that present-day conditions can trigger winters as cold as that record in spite of global warming. The atmospheric circulation that prevails during those events is analysed and compared to the observed circulation during the record-breaking events, showing no main change in the mechanisms leading to this type of extreme event.